Organizational justice, job satisfaction and Islamic spirituality among Malaysian SME employees - Abdul Manaf, Abdul Halim; Mohamed, Sulaiman; Othman, Abdul Kadir; Mhd. Sarif, Suhaimi (Korea Distribution Science Association, 2022)
The role of Islamic spirituality in the relationship between organizational justice (OJ) and job satisfaction is investigated in this study (JS). The three components of OJ in this study are distributive, procedural, and interactional justice. Islamic spirituality (IS) is founded on piety values, and IS was used as a moderating factor in this study to alter the link between OJ and JS among Malaysian employees of small and medium enterprises (SMEs). Four hundred sets of the questionnaire were issued using a simple random selection procedure, yielding 276 completed responses, suggesting a 69 percent response rate. Multiple Linear Regression Analysis (MLRA) was used to test the proposed relationships. The findings of the study demonstrate that the three OJ aspects have a considerable impact on employee JS, indicating the significance of these elements in ensuring that employees are satisfied with their jobs. IS, on the other hand, had no effect on the link between the OJ dimensions and JS. This research has added to the existing body of knowledge by giving further empirical evidence on the impact of OJ aspects on employee JS in SMEs, notably in Malaysia.